Risk of malignancy of BTA/RCPath Thyroid cytopathology diagnostic categories in a specialist cytopathology centre. (1st March 2022) - HOMER, Jarrod; Bowen, Alex; Enarche, Alina; Rana, Durgesh; Holbrook, Miles; Shelton, David
Abstract: Aim: Fine Needle Aspiration Cytology (FNAC) remains the primary determinant of management options for a patient with a U3-5 thyroid nodule. There is significant variation in risk of malignancy (ROM) between different centres, possibly reflecting the degree of specialist reporting and interpretation of RCPath guidance. The aims of this study is to report on ROM of FNAC categories in a specialist cytopathology centre. Methods: Consecutive thyroid FNAC results were analysed over 2 years (2017/18), all reported by dedicated cytopathologists and suspicious samples were peer reviewed. Cases suspicious for NIFTP/FVPTC were classified as Thy4. U-grade was recorded if classified during ultrasonography. Results were analysed with regard to histology available on thyroid surgery and/or clinical follow up. Results: There were 695 samples from 567 patients. The ROM in each category was: Thy1(6%); Thy2(1%), Thy3a(13%); Thy3f(11%); Thy4(27%); Thy 5(100%). In addition, 34/86 Thy3a nodules were subject to repeat FNAC, with 19 reported as Thy2, 7 as Thy3a again, 1 as Thy3f and 2 as Thy4 on second FNAC. We found that stratification of Thy3a-3f-4 by U grade did not help with risk stratification. Conclusions: Compared to the recent meta-analysis (Poller et al), we found a greatly reduced ROM in the Thy4 group (27% vs 79%), with smaller reductions in both Thy 3 groups in our specialised cytopathology centre. The reasons for this will be discussed. The descriptor of Thy 4 as "suspicious for malignancy" is inaccurate in our experience. Each centre should use their own figures when advising patients. Repeat FNAC for Thy3a lesions leads to >20% potentially avoiding surgery.